Association between family risk of stroke and myocardial infarction with prevalent risk factors and coexisting diseases. - Kennedy, R; Howard, G; Go, R; Rothwell, P; Tiwari, H; Feng, R; McClure, L; Prineas, R; Banerjee, A; Arnett, D (2012)
BACKGROUND AND PURPOSE: Familial transmission of stroke and myocardial infarction (MI) is partially mediated by transmission of cerebrovascular and cardiovascular risk factors. We examined relationships between family risk of stroke and MI with risk factors for these phenotypes. METHODS: A cross-sectional association between the stratified log-rank family score for stroke and MI with prevalent risk factors was assessed in the REasons for Geographic And Racial Differences in Stroke (REGARDS) cohort. RESULTS: Individuals in the fourth quartile of stratified log-rank family scores for stroke were more likely to have prevalent risk factors including hypertension (OR, 1.43; 95% CI, 1.30-1.58), left ventricular hypertrophy (OR, 1.42; 95% CI, 1.16-1.42), diabetes (OR, 1.26; 95% CI, 1.12-1.43), and atrial fibrillation (OR, 1.23; 95% CI, 1.03-1.45) compared with individuals in the first quartile. Likewise, individuals in the fourth quartile of stratified log-rank family scores for MI were more likely to have prevalent risk factors including hypertension (OR, 1.57; 95% CI, 1.27-1.94) and diabetes (OR, 1.29; 95% CI, 1.12-1.43) than the first quartile. In contrast to stroke, the family risk score for MI was associated with dyslipidemia (OR, 1.38; 95% CI, 1.23-1.55) and overweight/obesity (OR, 1.22; 95% CI, 1.10-1.37). CONCLUSIONS: Family risk of stroke and MI is strongly associated with the majority of risk factors associated with each disease. Family history and genetic studies separating nonspecific contributions of intermediate phenotypes from specific contributions to the disease phenotype may lead to a more thorough understanding of transmission for these complex disorders.